Complications associated with remote work during the COVID-19 pandemic: a rapid review: Complicaciones asociadas al trabajo remoto durante la pandemia COVID-19: una revisión rápida - Cruz-Ausejo, Liliana (2022)
This review identifies and describes the main outcomes and complications associated with remote work during the COVID-19 pandemic. A systematic review of the literature was carried out. This included observational studies whose population or partly carried out remote work, published between March 1, 2020, and November 30, 2020. The descriptors were adapted to MEDLINE (Ovid), EMBASE, Scopus and PsycINFO databases. We found 139 studies; 15 articles were included in this synthesis. A total of 18,818 remote workers were reported, of which women represented between 18.2%-100%. The findings describe the increased use of electronic devices, sedentary lifestyle, anxiety, depression, feelings of loneliness, sleep disorders and the presence of musculoskeletal pain in remote workers. Therefore, it is necessary to provide assistance and education to the remote worker in order to improve their conditions, reduce the associated complications and positively impact their lifestyle.